Evolution of Immune Checkpoint Blockade–Induced Myocarditis Over 2 Years - Norwood, Timothy G. (JACC Case Rep, 2020)
Ipilimumab and nivolumab for melanoma induced smoldering myocarditis remitting with steroids. Rechallenge with nivolumab produced steroid-refractory myocarditis confirmed by electron microscopy. Tacrolimus and mycophenolate transiently reduced inflammation, but antithymocyte globulin induced remission. Cardiomyopathy with fatty infiltration ensued, but the patient succumbed to rampant melanoma progression after lymphocyte depletion. (Level of Difficulty: Advanced.)